MIMICRY AND HYBRIDITY OF HOBBS IN DAVID LEITHC’S FAST AND FURIOUS: HOBBS AND SHAW (2019) MOVIE SCRIPT - Inkarani Inkarani Indrastuti; Heri Dwi Santoso; Yesika Maya Ocktarani (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
The purpose of the research is to determine the mimicry and hybridity issues that contained in the Fast and Furious: Hobbs and Shaw (2019) movie script, which focus on the main character Luke Hobbs, and the diplomatic relation between U.S States and Samoa as the setting for the Fast and Furious: Hobbs and Shaw (2019) movie. The kind of the research is library research that all of the data are collected from a movie script. The data is Fast and Furious: Hobbs and Shaw (2019) movie script and the type of the method that uses is descriptive method. The frame of mind in the research is to examine postcolonial issues using the theory of Homi K. Bhabha, we will learn about the mimicry and hybridity of Luke Hobbs.The results of the research indicate that there are mimicry and hybridity issues in the character Luke Hobbs, who is a native Samoa who lives and adapts well in United States. Bhabha’s postcolonial theory becomes an analytical equipment to revisit that behind every country there will always be history and relation, moreover there is a term about western countries and eastern countries which always have the connotation of colonial and colonized countries.